Design and Development of an Interactive Virtual Tour for Enhancing Architectural Design Communication in Civil Engineering Projects - Ethan Carter; Olivia Bennett (Civil Engineering Science and Technology, 2026)
This study addresses the limitations of traditional two-dimensional (2D) architectural drawings in effectively communicating spatial design to diverse stakeholders in civil engineering projects. The research aims to design and develop an interactive virtual tour system and to evaluate its effectiveness in improving architectural design communication. A Design and Development Research approach was employed, consisting of analysis, design, development, testing, and evaluation stages. The system was developed using SketchUp, Lumion, and Unity, and evaluated by 24 participants, including 12 professional designers and 12 non-technical clients. Data were collected through observation, questionnaires, and interviews, and analyzed using descriptive statistics and paired-samples t-tests. The results show that the virtual tour significantly outperformed 2D drawings across all evaluation aspects, with usability scores of 4.6 ± 0.28 compared to 3.2 ± 0.45, aesthetics scores of 4.7 ± 0.25 compared to 3.5 ± 0.40, and interactivity scores of 4.6 ± 0.30 compared to 2.9 ± 0.50, all with p-values < 0.01. These findings indicate that the virtual tour enhances spatial understanding, user engagement, and communication clarity. The novelty of this study lies in the explicit integration of realistic three-dimensional rendering, interactive navigation, and user-centered design principles within a Design and Development Research framework, combined with empirical evaluation involving both technical and non-technical stakeholders in a real project context. This study contributes to both theory and practice by demonstrating that interactive virtual tours serve as an effective communication medium, reducing misinterpretation and supporting more informed decision-making in civil engineering design processes.